(untitled) (Journal of Philosophy Culture and Political Science, 2019)
This article describes the IV Congress of Leaders of World and Traditional Religions, held this year in Astana. The article also addresses the importance of discussion in the agenda of the congress of the issues, the impact it may have on the world community. The author analyze the actual problems that were discussed during the congresses. In addition, the author turned their attention to the fact that highly respected guests who came from all corners of the world appreciated the level of organization of the event. Keywords: dialogue, congress, tolerance, peace, stability